PENGARUH MEDIA BAHAN ALAM TERHADAP PERKEMBANGAN MOTORIK HALUS DI TK SANTA YOHANA ANTIDA SINTANG - Susilawati, Magdalena; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of natural material media on fine motordevelopment in children aged 4-5 years in the Santa Yohana Antida ThouretTemanang Kindergarten in Sintang district. The research method used is descriptive data with quantitative forms. research subjects were 18 children aged 4-5 years,sampling using non probability with purposive sampling technique. Then the researchdata on fine motor development was collected using the observation method usingobservation and documentation guidelines. The analysis technique uses descriptivestatistics and data analysis using inferential statistical analysis methods. The results ofdata analysis showed that there was an increase in fine motor development usingnatural media in the form of gravel, ripe lamtoro seeds, cempedak leaves, rubberleaves, cassava leaves and sand. Then based on calculations carried out with the helpof SPSS version 25, it is known that the value of t in the SPSS output after an analysistest (paired sample t-test) is obtained Sig (2-tailed) value of 0,000 smaller than (0.05)and whereas From the result of tcount, it is obtained the value of (8,245)> from t table(2,120). Sig (2-tailed) value <0.05 and t count> t table then Ha is accepted and Ho isrejected. So the results of the study show that natural media is very influential inimproving fine motor development in children aged 4-5 years in Santa Yohana AntidaThouret Temanang Kindergarten.Keywords: natural, fine motoric media